= e u + C = e x 2 +2x+3 + C. Of course, it is the same answer that we got before, using the chain rule backwards. In essence, the method of u-substitution is a way to recognize the
Here are 4 simple steps for u-substitution: Pick your “u”. This expression is the inside part of the chain rule and is usually the term inside a radical, power, Differentiate u u u
What Is U-Substitution?
Let u = x 3. Differentiating the expression, Using these results in the original integral equation, F(x)= ∫f(x)dx. F(x)= ∫3x 2 cos(x)dx. F(x)= ∫cosu du. F(x)= sin(u)+ C.
357
Specialists
88%
Recurring customers
111561+
Orders Deliver
People said
Excellent app! It is very helpful and convenient when stuck on a math problem or when you need to access whether your solutions are correct. This is the best Problem Solving app, totally recomand. Mad respect for it being free and helping me out in class, it easily calculates any math and answers in a very short time.